PENGARUH BEBAN KERJA DAN DAN WORK-LIFE BALANCE TERHADAP TURNOVER INTENTION PADA KARYAWAN PT KEDIRI INTERMEDIA PERS - Afifaturochmah, Lilis; Swasti, Ika Korika (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Companies that often ignore the needs and rights of human resources, as well as increasing work demands and working conditions that do not meet expectations, will trigger turnover intention in employees. This study aims to determine the effect of workload and work-life balance on PT. Kediri Intermedia Pers’ employees turnover intention. This research employs a quantitative methodology, utilizing a saturated sampling technique to select a sample of 44 respondents. The analysis technique in this study uses the SmartPLS3 program. From the results of statistical testing, it was found that workload has a positive effect on turnover intention, while work-life balance has a negative effect on turnover intention in employees of PT Kediri Intermedia Pers. Keyword : Workload; Turnover Intention; Work-Life Balance